Responses of Jumbo Quail to a Diet Containing Corticated Marama Bean (Tylosema esculentum) Meal Pre-Treated with Fibrolytic Multi-Enzymes - Mveleli Marareni; Chidozie Freedom Egbu; Cornelia Kedidimetse Lebopa; Caven Mguvane Mnisi (Life)
The nutritional utility of leguminous products such as corticated marama bean (Tylosema esculentum) meal (CMBM) in quail diets is limited by high fibre levels. This study evaluated the impact of dietary CMBM pre-treated with fibrolytic multi-enzyme (FMENZ) on growth performance, and physiological and meat quality responses in Jumbo Coturnix quail. Two hundred and forty 7-day-old Jumbo quail (29.4 ± 2.72 g initial live weight) were randomly distributed to five experimental diets, with six replicate cages each (eight birds/cage). The diets were a grower diet without CMBM, and the same grower diet plus 100 g/kg CMBM pre-treated with 0, 1, 1.5, and 2% (v/w) FMENZ. Positive quadratic responses (p < 0.05) were recorded for overall feed intake and body weight gain in weeks 2 and 3. The control diet promoted the highest (p < 0.05) gain-to-feed ratio in weeks 2 and 3, and the best weight gains and glucose levels, but reduced lipase levels. Final body weights declined linearly [p = 0.037] with FMENZ levels. Breast pH increased linearly, while haemoglobin and 1 h post-mortem chroma showed positive quadratic effects (p < 0.05) with FMENZ levels. The use of the enzymes did not improve the feed value of CMBM in Jumbo quail diets.